Lichen planus: A Systematic Review - Karolina Garbacz; Maria Maciąg; Małgorzata Pasztelan; Jarosław Pulikowski; Małgorzata Słaboń; Maciej Sobczyk; Aleksandra Muca; Aleksandra Marczak; Julia Krawczuk vel Walczuk; Joanna Baran (Kazimierz Wielki University, 2024)
Lichen planus (LP) is a chronic skin, mucous membrane, and nail disease. Lichen planus is a rare skin condition occurring in less than 1% of the general population, affecting both children and adults. Oral lichen planus (OLP) involvement is much more common. It is an autoimmune disease  caused by T lymphocytes, with epigenetic factors playing a significant role in the development of autoimmune skin diseases. MicroRNAs (miRNAs), a group of non-coding RNAs, play a substantial role in regulating the immune response.1 The etiology of lichen planus in not fully understood. It can be triggered by antihypertensive drugs, beta-blockers, infections, viral hepatitis, psychological stress, and others. Cases of lichen planus appearing after recovering from COVID-19 have been reported, as well as a significant increase in cases after COVID-19 vaccination.2-5 Diagnosis is based on clinical presenstation and characteristic histopathological findings. The disease is often self-limiting, accompanied by persistent itching and painful erosions of the mucous membrane, affecting the patient's quality of life and mental well-being. First-line treatments inculde topical corticosteroids and/or oral corticosteroids. There are reports of new potential treatments, such as biologic drugs (anti-IL12/13, anti-IL17) and Janus kinase inhibitors. Consequently, a dramatic change in lichen planus treatment can be expected in the near future. The majority of patients suffering from lichen planus develop metabolic syndrome which is the cause of other diseases. This article provides a comprehensive overview of current knowledge about lichen planus and its variants.